THE EFFECT OF WORK ENVIRONMENT, MOTIVATION AND WORK STRESS ON JOB SATISFACTION OF PT. KYOKUYO INDUSTRIAL INDONESIA - Rismawati Rismawati; Suriyanti Suriyanti (Jurnal Ekonomi, 2022)
This study was conducted to determine the effect of work environment on job satisfaction, whether there is an effect of motivation on job satisfaction, and whether there is an effect of job stress on job satisfaction. The sampling method used is non-probability sampling, namely the purposive sampling method with a total sample of 67 people. Data collection techniques include observation, distributing questionnaires and literature study. Using a questionnaire distributed to employees, it has been tested using SPSS 25. The results of the analysis obtained by the researcher using the t-test partially are that the work environment gets a tcount value of 2,553, motivation gets a tcount value of 4,009, and work stress gets a tcount value of 3,690. The results of this study prove that the work environment has a positive and significant effect on employee job satisfaction, motivation has a positive and significant effect on employee job satisfaction, and job stress has a positive and significant effect on employee job satisfaction at PT Kyokuyo Industrial Indonesia. Simultaneous f test the effect of work environment, motivation and work stress have a positive and significant effect on job satisfaction which is shown from the calculated f of 6.017 with a significance of 0.000. The value of the coefficient of determination is 0.626, which means that the work environment, motivation and job stress affect job satisfaction 62.6% and the remaining 37.4% is influenced by other factors outside the research variables.